Alarin in cranial autonomic ganglia of human and rat. (February 2015) - Schrödl, Falk; Kaser-Eichberger, Alexandra; Trost, Andrea; Strohmaier, Clemens; Bogner, Barbara; Runge, Christian; Bruckner, Daniela; Krefft, Karolina; Kofler, Barbara; Brandtner, Herwig; Reitsamer, Herbert A.
Abstract: Extrinsic and intrinsic sources of the autonomic nervous system contribute to choroidal innervation, thus being responsible for the control of choroidal blood flow, aqueous humor production or intraocular pressure. Neuropeptides are involved in this autonomic control, and amongst those, alarin has been recently introduced. While alarin is present in intrinsic choroidal neurons, it is not clear if these are the only source of neuronal alarin in the choroid. Therefore, we here screened for the presence of alarin in human cranial autonomic ganglia, and also in rat, a species lacking intrinsic choroidal innervation. Cranial autonomic ganglia (i.e., ciliary, CIL; pterygopalatine, PPG; superior cervical, SCG; trigeminal ganglion, TRI) of human and rat were prepared for immunohistochemistry against murine and human alarin, respectively. Additionally, double staining experiments for alarin and choline acetyltransferase (ChAT), tyrosine hydroxilase (TH), substance P (SP) were performed in human and rat ganglia for unequivocal identification of ganglia. For documentation, confocal laser scanning microscopy was used, while quantitative RT-PCR was applied to confirm immunohistochemical data and to detect alarin mRNA expression. In humans, alarin-like immunoreactivity (alarin-LI) was detected in intrinsic neurons and nerve fibers of the choroidal stroma, but was lacking in CIL, PPG, SCG and TRI. In rat, alarin-LI was detected in only a minority of cranial autonomic ganglia (CIL: 3.5%; PPG: 0.4%; SCG: 1.9%; TRI: 1%). qRT-PCR confirmed the low expression level of alarin mRNA in rat ganglia. Since alarin-LI was absent in human cranial autonomic ganglia, and only present in few neurons of rat cranial autonomic ganglia, we consider it of low impact in extrinsic ocular innervation in those species. Nevertheless, it seems important for intrinsic choroidal innervation in humans, where it could serve as intrinsic choroidal marker. Highlights: Alarin is present in neurons and nerve fibers of the human choroid. Alarin is absent in human cranial autonomic ganglia supplying the eye. Alarin serves as intrinsic choroidal marker in humans. Alarin is absent in rat cranial autonomic ganglia supplying the eye.